MSX1 and PAX9 genetic alteration in Malaysian families with hypodontia - Lestari, Widya; Ardini, Yunita Dewi; Muhamad Zamil, Nabilah; Mohamed Yussof, Nor Aini; Idrus, Erik (Ektodermal Displazi Grubu, 2017)
Hypodontia is characterized by the absence of one to six teeth. Malaysia has a high prevalence of hypodontia (2.8%). This study aimed to investigate the MSX1 mutation with clinical variability in Malaysian hypodontia families and to correlate the findings a previous study of the PAX9 mutation. Materials and methods: We re-examined seven individuals from two families of the previous PAX9 study. Orthophantomogram (OPG) and intraoral photos were re-assessed. Saliva was collected for genetic analysis. Direct sequencing was done on exons 1 and 2 of MSX1 and exons 2 and 3 of PAX9. Results: In family 1, three out of five members are affected. The mother has posterior hypodontia, while the daughters have anterior hypodontia. Point mutations on exon 1 of MSX1 (c.599C>T, c.732G>A) and on exon 3 of PAX9 (c.477delG, c.480delT) were identified on 1B (mother) and 1D (second daughter). Her carrier-son (1E) exhibited c.597C>T, c.730G>A on exon 1 of MSX1 and c.273T>G on exon3 of PAX9. In family 2, the daughter has a missing lower premolar with a point mutation on exon 1 of MSX1 (c.730G>A). A similar point mutation in her nonhypodontia father on exon 2 of PAX9 (c.628C>T) was observed. Conclusion: Mutation of MSX1 is observed in familial hypodontia; both genes MSX1 and PAX9 are needed to manifest hypodontia whereby PAX9 is the predominant gene mutation.